Recent developments in trade between Jamaica and the Republic of Trinidad-Tobago - Johnson, Anthony S. (The Author KingstonJM, 1996)
Investigates the reasons for the rapid strides being made by produce from Trinidad and Tobago in the Jamaican market-place, at a time when many Jamaican manufacturing plants were being closed, or cutting back production.